Prospective observational study to evaluate treatment satisfaction and effectiveness in patients with relapsing multiple sclerosis starting cladribine tablets (CLADREAL) in Italy - Filippi, Massimo; Ferrè, Laura; Zanetta, Chiara; Rizzi, Caterina; Pessina, Gabriella; Assogna, Francesco; Rocca, Maria A. (Frontiers in Neurology, 2024)
Disease-modifying therapies (DMTs) for multiple sclerosis (MS) reduce relapse frequency, magnetic resonance imaging (MRI) activity, and slow disability progression. Numerous DMTs are approved for relapsing forms of MS although real-world data on patient-reported outcomes (PROs) and quality of life (QoL) are needed to inform treatment choice. Immune reconstitution therapy with cladribine tablets is a highly effective treatment for relapsing MS (RMS). We present the protocol for an observational study to prospectively assess the effectiveness of cladribine tablets on clinical and MRI parameters as well as on PROs, including treatment satisfaction, QoL, sleep quality, self-perceived health, fatigue, and physical function. Enrolled patients at study sites in Italy will be adults with RMS (including relapsing–remitting and active secondary progressive MS) who are either treatment naïve or have received at least one first-line disease modifying DMT or no more than one second-line DMT. The primary objective will be change in global treatment satisfaction measured with the Treatment Satisfaction Questionnaire for Medication Version 1.4 approximately 24 months after initiating cladribine tablets in patients switching from previous DMTs. Secondary objectives will include global treatment satisfaction at earlier timepoints, will comprise treatment naïve patients, and will quantify treatment effectiveness and tolerability. We will also assess relapses, disability progression, MRI activity, and other PROs at approximately 12 and 24 months. The findings will provide insight from daily clinical practice into the patient’s experience to complement data from controlled trials and inform treatment choice. EU PAS Registration Number EUPAS49334 filed 17/10/2022.